2016
DOI: 10.4103/2008-7802.190611
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of endocrine system affectation in fisher 344 rats by food intake exposed with malathion, applying naïve bayes classifier and genetic algorithms

Abstract: Background:Reported cases of uncontrolled use of pesticides and its produced effects by direct or indirect exposition, represent a high risk for human health. Therefore, in this paper, it is shown the results of the development and execution of an algorithm that predicts the possible effects in endocrine system in Fisher 344 (F344) rats, occasioned by ingestion of malathion.Methods:It was referred to ToxRefDB database in which different case studies in F344 rats exposed to malathion were collected. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…MAL is not listed as a primary thyroid toxic chemical. However, recent evidence found that MAL affected thyroperoxidase catalyzed iodide oxidation, which affected thyroid hormone transportation and increased incidence of parathyroid hyperplasia (Mora et al 2016;Xiong et al 2018). The effect of MAL on the thyroid gland in humans was supported by a study reporting the association between hypothyroidism and MAL in male applicators (Goldner et al 2013).…”
Section: Effect Of Malathion On the Thyroid Glandmentioning
confidence: 98%
“…MAL is not listed as a primary thyroid toxic chemical. However, recent evidence found that MAL affected thyroperoxidase catalyzed iodide oxidation, which affected thyroid hormone transportation and increased incidence of parathyroid hyperplasia (Mora et al 2016;Xiong et al 2018). The effect of MAL on the thyroid gland in humans was supported by a study reporting the association between hypothyroidism and MAL in male applicators (Goldner et al 2013).…”
Section: Effect Of Malathion On the Thyroid Glandmentioning
confidence: 98%